Electrochemical DNA-sensor for evaluation of total antioxidant capacity of flavours and flavoured waters using superoxide radical damage - Barroso, M. Fátima (2013)
In this paper, a biosensor based on a glassy carbon electrode (GCE) was used for the evaluation of the total antioxidant capacity (TAC) of flavours and flavoured waters. This biosensor was constructed by immobilising purine bases, guanine and adenine, on a GCE. Square wave voltammetry (SWV) was selected for the development of this methodology. Damage caused by the reactive oxygen species (ROS), superoxide radical (O2·−), generated by the xanthine/xanthine oxidase (XOD) system on the DNA-biosensor was evaluated. DNA-biosensor encountered with oxidative lesion when it was in contact with the O2·−. There was less oxidative damage when reactive antioxidants were added. The antioxidants used in this work were ascorbic acid, gallic acid, caffeic acid, coumaric acid and resveratrol. These antioxidants are capable of scavenging the superoxide radical and therefore protect the purine bases immobilized on the GCE surface. The results demonstrated that the DNA-based biosensor is suitable for the rapid assess of TAC in beverages.